TOURISTIC VILLAGE IN VALCEA - PROMOTER OF ETNOFOLKLORE TOURISM IN ROMANIA - Maria-Roxana, Dorobantu (Strategii Manageriale)
This paper discusses perception and links of ethnofolklore potential from Romania, in general, and from Valcea County, in particular. The purpose of this paper is to show the link between rural tourism and ethnofolklor which can help on promoting this form of tourism which is rural tourism. In the paper is analized the perceived benefits of ethnofolklor by examining the importance of this activity in accomplishing with ethnofolklor and rural tourism This paper links changes at the local, rural community level to broader, more structural considerations of globalization and allows for a deeper, more theoretically sophisticated consideration of the various forces and features of rural tourism development. This paper considers the extent to which a relationship exists between rural tourism and spiritual experiences connected to ethnofolklore potential.